Socio-economic factors as determinants of employees’ commitment in a selected organization in Ibadan (2022)
The commitment of employees in an Organization is very important especially in Service providing public Organization. Despite various studies on the determinants of employees' commitment, little studies have examined the influence of socio-economic factors on employees' commitment. This study therefore, investigates employees' educational qualification and income on commitment in a selected Organization in Ibadan. The study adopted descriptive design with multi-stage sampling techniques. About 250 employees were selected into the study, their ages ranged between 20 and 59years, mean of 41.7 white Standard deviation of 8.27. Structured questionnaire was used for data collection. The result showed that educational qualification significantly influenced employee's commitment (F[5,249] =3.05;P<05). Employees with primary school certificate (x=61.00; SD=0.01) significantly different from other employees with OND/NCE (x Diff=15.26; Std Error=6.13; P<.05), B.Sc./BEn/BA (x Diff.=15.01; Std Error=6.10; P<.05), and Postgraduate (x_Diff.= 16.94; Std Error=6.22; P<.05); however, not significantly different from employees with SSCE (x Dijf.=10.27; Std Error=6.57; P>.05) on employees' commitment. Therefore, employees with primary school certificates contributed to the significance of educational qualification on employees' commitment. More so, income significantly predicts employee commitment (R2=.14, R=.38; ß=.38; F (1,248) = 41.75; P<.01). The income of employees accounted for 14% variance that occurred in employees' commitment. The study concluded that income of the employees including their bonus, allowances and other benefits should be closely paid attention to, while considering educational qualification of the employees especially when recruiting and allocating employees into job units